2018
DOI: 10.1016/j.neuron.2018.01.031
|View full text |Cite
|
Sign up to set email alerts
|

TREM2 Is a Receptor for β-Amyloid that Mediates Microglial Function

Abstract: Mutations in triggering receptor expressed on myeloid cells 2 (TREM2) have been linked to increased Alzheimer's disease (AD) risk. Neurobiological functions of TREM2 and its pathophysiological ligands remain elusive. Here we found that TREM2 directly binds to β-amyloid (Aβ) oligomers with nanomolar affinity, whereas AD-associated TREM2 mutations reduce Aβ binding. TREM2 deficiency impairs Aβ degradation in primary microglial culture and mouse brain. Aβ-induced microglial depolarization, K inward current induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
477
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 520 publications
(528 citation statements)
references
References 44 publications
20
477
0
Order By: Relevance
“…Moreover, decreased membrane‐bound TREM2 is associated with reduced uptake of Aβ (Zhao et al . ). To determine levels of Aβ 1‐42 and1‐40 in the brains of our cohort, we analyzed brain lysates using the Aβ triplex Mesoscale Discovery kit.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, decreased membrane‐bound TREM2 is associated with reduced uptake of Aβ (Zhao et al . ). To determine levels of Aβ 1‐42 and1‐40 in the brains of our cohort, we analyzed brain lysates using the Aβ triplex Mesoscale Discovery kit.…”
Section: Resultsmentioning
confidence: 97%
“…; Zhao et al . ). Microglia survey the environment for cues on the disease state, interacting with extracellular milieu, other glial cells, and neurons (Tang and Le ).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, upon evaluating the levels of CD68 and Lgals3 protein markers showing microglial phagocytosis, they found a significant increase in microglial‐associated Aβ phagocytosis in the cortex of 5xFAD/TREM2 mice, which is in agreement with the other in vitro study (Zhao et al . ) indicating the knockdown of TREM2 expression decreased Aβ clearance. In addition, Li et al .…”
Section: Microbial Amyloidsmentioning
confidence: 93%
“…) and in vitro (Zhao et al . ) studies performed simultaneously in two different laboratories. In these studies, it was shown that microbial amyloids act as a TREM2 ligand and that increasing level of TREM2 expression in BAC transgenic mice expressing human TREM2 (BAC‐TREM2) can significantly increase the degradations of Aβ 40 and Aβ 42 loads, which result in an improvement in AD phenotype; furthermore, upon examining the structures of Aβ plaques, they observed that Aβ plaques were mainly in inert form rather than the filamentous structure in 5xFAD/TREM2 mice.…”
Section: Microbial Amyloidsmentioning
confidence: 99%